E-024 Intra-arterial Vasodilator Therapy for Severe Vasospasm in Acute Bacterial Meningitis. (14th July 2013) - Taqui, A; Burgess, R; Hui, F; Toth, G
Abstract : Introduction and Purpose: Cerebrovascular complications of acute bacterial meningitis may include vasculitis, vasospasm, venous and arterial thrombosis, intracranial aneurysm formation and others. These complications have been shown to be important predictors of prognosis. The role of invasive endovascular therapies has not been well studied for meningitis-related vasospasm. We present a patient with acute bacterial meningitis who received intra-arterial (IA) vasodilator therapy to arrest worsening intracranial vasculopathy. Materials and Methods: Case report and review of literature. Results: A 38 year old male with history of recurrent ear infections presented to the hospital with depressed mental status and fever requiring intubation. He was diagnosed with diffuse cerebral oedema, hydrocephalus, left mastoiditis, and severe Streptococcus Pneumoniae meningitis and ventriculitis. He was administered antibiotics, steroids and seizure prophylaxis. An extraventricular drain was placed. The patient underwent mastoidectomy. MRI brain on day 5 showed acute infarcts in bilateral inferior cerebellar hemispheres. Noninvasive MRA study on day 7 was suggestive of only mild vasocontrictive segments in anterior and posterior circulations. He was started on nimodipine and triple-H therapy. On day 9, patient developed bradycardia, worsened mental status and motor deficits. A CTA brain demonstrated significant narrowing of the vertebrobasilar system with associated new scattered infarcts on MRI. An angiogram confirmed severe vasospasm in the distal vertebral arteries, basilar artery, and moderate vasospasm in bilateral supraclinoid internal carotid arteries. IA verapamil was infused in these vasospastic regions with improved vessel calibre and distal flow. The patient's neurological exam also improved after the intervention. A followup angiogram on day 14 revealed further improvement in the intracranial vasospasm. Conclusion: Vasospasm causing delayed ischaemic neurologic deficit is a rare, but severe cerebrovascular complication of acute bacterial meningitis. It can be a significant predictor of prognosis, and the disease may progress despite maximal medical therapy. Interventional therapy may be an important adjunctive treatment along with conservative medical modalities. Disclosures: A. Taqui: None. R. Burgess: None. F. Hui: None. G. Toth: None.